SAFAT PEMESINAN 10 JENIS KAYU DARI DAERAH SULAWESI UTARA - Sri Rulliaty; osly rachman (Jurnal Penelitian Hasil Hutan, 1991)
machining properties of ten wood species from north Sulawesi was studied. the sampie  materiawas tested using ASTM D-1666-64, that was modified to forest products researeh institute report No. 160 (1982). firatiy,the;samples (25 pieoes/species) were dried to an equilibrium moisture content condition (15 or 18 % of MC). the machine-ing properties examined were paining, shaping, boring,turning and the percentage wood defect recorded.                the result shows that, five wood species has fair to very good machining properties i.e.Dysoxylum sp. elmerillia ovalis, lophopetalum javenicum,pangium edule and serianthes minahassae.the remainders has good to very good machine-ing properties, whereas three wood secies i.e. aglaia versteghii.lapiacea subintegerrima and neonaudes sp. better than others.